2010 35th IEEE Photovoltaic Specialists Conference 2010
DOI: 10.1109/pvsc.2010.5614729
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the first flight experiment with dedicated space CIGS cells onboard the Delfi-C3 nanosatellite

Abstract: In this paper we analyze and explain the performance of CIGS on Ti cells which have been mounted in the Dutch Delfi-C 3 nanosatellite that was launched in April 2008. The CIGS experiment includes several novel technologies for thin film solar cells in space. A new interconnect method based on pressure contacts between the cells was developed to minimize stresses between the electrical contacts. A thin protective coating was developed especially for a high emissivity. An electrical model is presented to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Deployable solar panels increase power generation. 3,4 Anyway, the deployment of solar panels clearly changes the position of the mass centre for the whole satellite, which may help to improve, or to hinder, the stability and attitude of the satellite, depending on the design strategy of attitude determination control system (ADCS) subsystem (deployable boom). They also allow the integration of some other devices such as high-gain antennas to increase communication capabilities.…”
Section: In 2009 California Polytechnic State University (Calpoly) Andmentioning
confidence: 99%
“…Deployable solar panels increase power generation. 3,4 Anyway, the deployment of solar panels clearly changes the position of the mass centre for the whole satellite, which may help to improve, or to hinder, the stability and attitude of the satellite, depending on the design strategy of attitude determination control system (ADCS) subsystem (deployable boom). They also allow the integration of some other devices such as high-gain antennas to increase communication capabilities.…”
Section: In 2009 California Polytechnic State University (Calpoly) Andmentioning
confidence: 99%
“…Delamination, of thin film PV for space applications, has been considered to be of particular concern to the research community since a research programme, conducted by Dutch Space B.V., investigating thin film copper indium gallium diselenide (CIGS), on titanium foil, suffered delamination from the substrate at the interconnects when subject to the thermal cycling that might be encountered in space 7 . However, after these results, new interconnects were developed and a flight experiment conducted on the Delfi‐C 3 , 3‐unit CubeSat in a LEO 8 . The CIGS cells, on titanium foil, showed no signs of degradation over the initial 3‐month monitoring period during which time they were subject to temperature changes of 70°C twice a minute due to the quick rotation of the CubeSat and the cells' low heat capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The CIGS cells, on titanium foil, showed no signs of degradation over the initial 3‐month monitoring period during which time they were subject to temperature changes of 70°C twice a minute due to the quick rotation of the CubeSat and the cells' low heat capacity. This demonstrated that the revised interconnect method had resolved the delamination issue 8 . More recently (2018), Ascent Solar Technologies, Inc. have developed a prototype flexible CIGS module, which has been delivered to the International Space Station for a 1 year in‐orbit assessment of the technology 9…”
Section: Introductionmentioning
confidence: 99%
“…Several holding and release mechanisms have been developed and used to hold and release the deployable solar panels of a CubeSat [7,8]. In commercial satellites and aerospace engineering, pyrotechnic devices have been used in the HRMs.…”
Section: Introductionmentioning
confidence: 99%